Resolving Zero Divisors Using Hensel Lifting - Kluesner, John; Monagan, Michael (2017 19th International Symposium on Symbolic and Numeric Algorithms for Scientific Computing (SYNASC), 2017)
Algorithms which compute modulo triangular sets must respect zero divisors. We present Hensel lifting as a tool for resolving them. We give an application: a modular algorithm for computing gcds of univariate polynomials with coefficients modulo a radical triangular set over the rational numbers. We have implemented our algorithm using Maple's RECDEN package. We compare our implementation with the procedure RegularGcd in the RegularChains package.